Invitro Micro Encapsulation of Beta Tri Calcium Phosphate from Anadara granosa Shell Synthesis - Diana Soesilo; Aprilia; Moh. Basroni Rizal (Denta Journal Kedokteran Gigi, 2020)
Background: Calcium is a material that is mostly contained in the Anadara-granose shell. Beta-TCP can be obtained from the hydrothermal process from the Anadara-granose shell. Beta-TCP has a chemical composition that approximates the structure of bones and teeth. Objective:The microencapsulation technique aims to increase stability, reduce side effects and toxic effects of drugs, and prolong the release of ingredients. The encapsulation process is an attempt to inhibit the dissolution speed of Calcium to prevent tunnel defects. Methods: Anadara-granose shell powder was subjected to hydrothermal processing for 18 hours and sintering for 3 hours. The beta-TCP powder was dissolved with aquadest using a magnetic stirrer until it was homogeneous, Na-alginate was dissolved in aquadest until it was homogeneous with a magnetic stirrer then the two solutions were mixed and the CaCl2 solution was dropped. The sample was divided into 3 groups; Pure Beta-TCP(K-); 7 hours stirring (P1); 8 hours stirring (P2). After completion of the stirrer, the samples were centrifuged at 2500 rpm for 6 minutes, then freeze-dried for 12 hours. The level test was carried out using complexometry comparing the pure Beta-TCP group with the Beta-TCP stirrer encapsulation process for 7 hours and 8 hours. Results: The data showed that the average calcium level in K(-) group with pure Beta-TCP was 8.63%, the P1 Beta-TCP group with 7 hours stirrer 2.86%, and the P2 Beta-TCP group with 8 hours stirrer 2.12%. Conclusion: In the Anadara-granosa shell nanoencapsulation process, the calcium level gradually decreased with the longer duration of stirring time